Exploring metabolic vulnerability and therapeutic potential in cancers with isocitrate dehydrogenase mutations - Hvinden, IC (2022)
Treatment of mutant isocitrate dehydrogenase 1 (IDH1) glioma remains challenging; targeted allosteric inhibitors currently provide limited clinical effect. Resistance to mutIDH1 inhibitors has also emerged in other cancers with mutant IDH1. IDH1 catalyses the decarboxylation of isocitrate to 2-oxoglutarate (2-OG) and concomitant reduction of NADP+ to NADPH. Upon mutation, the enzyme instead reduces 2-OG to (R)-2-hydroxyglutarate (2 HG) with NADPH. 2 HG accumulates to high levels in cells and is thought to promote tumorigenesis by e.g., disrupting DNA and histone methylation and impairing DNA repair. Altered central carbon, amino acid and lipid metabolism, as well as redox homeostasis, has been linked to expression of mutIDH1R132H and presence of high levels of 2-HG. Yet, the understanding of the mechanisms by which 2 HG affects metabolism, and what capacity those metabolic changes have to drive tumorigenesis, remains limited. A more detailed comprehension of the metabolic changes in mutIDH1 glioma and how they relate to 2-HG abundance would improve understanding of tumorigenesis and potentially uncover new therapeutic targets. The aim of this thesis was therefore to investigate mutIDH1 glioma metabolism by comparison to a matched wild-type (wt) IDH1 model and with metabolic inhibitors targeting the mutated enzyme or substrate availability.